Health Literacy Level Regarding Covid-19 Vaccination for Health and Non-Health Students At UIN Alauddin Makassar 2022 - Eva Yustilawati; Nurul Fadhilah Gani; Aidah Fitriani; Eka Hadrayani (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2023)
Background: Covid-19 vaccination is carried out to accelerate the handling of Covid-19. Individuals must have good health literacy in seeking information and making vaccination decisions, not only medical officers, but all communities and students. It is necessary to evaluate the level of health literacy to the Health and Non-Health students. Methods: This research is a quantitative comparative study, cross sectional design. There were 500 participants with 299 Health students and 210 Non-Health students. Data were collected through questionnaires using the HLQ questionnaire (Health Literacy Quisioner). Data were analyzed with the Kruskal Wallis test. Results: Based on statistical analysis, the level of health literacy of UIN Alauddin Makassar students is in good category with a mean score of 3-4. There is a difference about health literacy understanding between Health and Non-Health students (p-value 0.001). Domains is needed to be improved in terms of finding appropriate health services and communication with health workers. Conclusion: There is a difference about health literacy understanding between Health and Non-Health students of UIN Alauddin Makassar and it is necessary to carry out strategies to improve the health literacy.